Simplified Technique of Conventional Cholecystectomy in a Patient with Situs Inversus Totalis: A Case Report from Nepal - Nag, Suresh Kumar (Journal of Nepalgunj Medical College, 2022)
Introduction: Situs inversus is a rare autosomal recessive disorder occurring in 1:5,000 to 1:20,000 indiviuals. Cholecystectomy is a standard treatment for symptomatic gallbladder stone. We report a case of cholelithiasis in patient with inversus totalis who underwent cholecystectomy.Case presentation: A 48 years old obese female patient with dextrocardia and hypertention presented with a recurrent left upper abdominal pain for two years. Ultrasound abdomen showed gallbladder stone. Conventional cholecystectomy was done with a small left subcostal incision. The postoperative period was uneventful and the patient was discharged on 3rd post operative day.Conclusion: Cholecystectomy is the treatment of choice in patients with a left sided gallbladder stone, like in normal gallbladder and it is safe.